The Influence of Effectiveness and Efficiency of Use of Accounting Information Systems on Company Performance at CV. Prima Independent - Wijayanti, Mella; Widiawati, Hestin Sri; Puspita, Erna (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This research was conducted with the aim of determining the effect of the effectiveness and efficiency of using an accounting information system on company performance at CV Prima Mandiri as one of the companies that uses an accounting information system. Design/Method/Approach: The subjects in this research were CV Prima Mandiri employees as users of the accounting information system implemented in the company. This research uses a causal quantitative approach with analytical instruments in the form of multiple linear regression analysis and hypothesis testing using the t test, F test and determination test. Research Finding: The results of the research show that the effectiveness and efficiency variables in the use of accounting information systems have a significant effect, both partially and simultaneously, on company performance at CV Prima Mandiri.